Pathology of natural cases of ovine pulmonary adenocarcinoma (Jaagsiekte) in goats - Devi, V. Rama; Manasa, B.B.; Samatha, V.; Mahesh, M.; Srikanth, K.V.; Yathiraja Rao, T.; Satheesh, K.; Nanda Kishore, K.V.S. (Brazilian Journal of Veterinary Pathology, 2016)
The pathological findings and the immunohistochemical and molecular diagnosis of two natural cases of pulmonary adenocarcinoma in goats are described. Ovine pulmonary adenocarcinoma (OPA), a contagious lung tumor, caused by an exogenous Jaagsiekte Sheep Retrovirus (JSRV), is reported commonly in sheep and rarely in goats. The affected lungs had a focally extensive and firm nodule or multiple nodules on the cranioventral region. On the cut surface, the nodules were greyish, granular and moist, resembling classical form of OPA. Microscopically, the lung sections showed unencapsulated nodules of neoplastic epithelial cells, from alveoli and bronchioles, forming papillary projections or acini. On the immunohistochemical analysis, JSRV capsid protein was demonstrated in the neoplastic epithelial cells. Genomic DNA was extracted from the lung tumor tissues and was subjected to U3-hn-PCR that further confirmed the presence of JSRV. The pathological findings in goats were similar to that of OPA affecting lungs of sheep and, to the author’s knowledge, this is the first report of the disease in goats with immunohistochemical and PCR confirmation of JSRV.